A study of interference between bluetooth and 802.11b (WIFI) / Mazani Manaf, Md Jamil Abu Sari and Jamaludin Md Yusof - Manaf, Mazani; Abu Sari, Md Jamil; Md Yusof, Jamaludin (2005)
WIFI (802.1 lb) and Bluetooth are the most common worldwide wireless standards. Both operate in the 2.4 GHz ISM band. Interference occurs while both WIFI and Bluetooth are operating concurrently in a shared environment. WIFI and Bluetooth devices suffer and loss its performance due to the interference. This is because of the collision of frequency for both devices which used the same radio frequency. WIFI is based on DSSS frequency modulation while Bluetooth is based on FHSS frequency modulation. Although these wireless standards have its own hopping technique, unfortunately interference still occurs. This performance degradation brings dissatisfaction to wireless users. Thus, a wireless network traffic analysis is conducted to determine which wireless standards suffer most from the interference. The wireless network traffic analysis consists of three phases. First phase measures the baseline performance, second phase measures the performance with interferer devices which are placed nearby and the third phase measures the wireless performance with interferer devices which are placed away. The performance of the wireless is measured and analyzed from the aspect of wireless throughput, bandwidth and response time. The outcome of the analysis and findings are used to determine the relation and the best wireless standard for a specific environment. It also discusses ways on how to reduce interference and implement wireless network with minimal effect of interference.